Review of a two-year methicillin-resistant Staphylococcus aureus screening program and cost-effectiveness analysis in Singapore. Issue 1 (December 2015) - Win, Mar-Kyaw; Soliman, Tarek; Lee, Linda; Wong, Chia; Chow, Angela; Ang, Brenda; Roman, Carrasco; Leo, Yee-Sin
Abstract Background Methicillin-resistantStaphylococcus aureus (MRSA) poses an increasingly large disease and economic burden worldwide. The effectiveness of screening programs in the tropics is poorly understood. The aims of this study are: (i) to analyze the factors affecting MRSA colonization at admission and acquisition during hospitalization and (ii) to evaluate the cost-effectiveness of a screening program which aims to control MRSA incidence during hospitalization. Methods We conducted a retrospective case–control study of patients admitted to the Communicable Disease Centre (CDC) in Singapore between Jan 2009 and Dec 2010 when there was an ongoing selective screening and isolation program. Risk factors contributing to MRSA colonization on admission and acquisition during hospital stay were evaluated using a logistic regression model. In addition, a cost-effectiveness analysis was conducted to determine the cost per disability-adjusted life year (DALY) averted due to implementing the screening and isolation program. Results The average prevalence rate of screened patients at admission and the average acquisition rate at discharge during the study period were 12.1 and 4.8 % respectively. Logistic regression models showed that older age (adjusted odds ratio (OR) 1.03, 95 % CI 1.02–1.04, p  < 0.001) and dermatological conditions (adjusted OR 1.49, 95 % CI 1.11–1.20, p  = 0.008) were independently associated with an increased risk of MRSA colonization at admission. Age (adjusted OR 1.02, 95 % CI 1.01–1.03, p  = 0.002) and length of stay in hospital (adjusted OR 1.04, 95 % CI 1.03–1.06, p  < 0.001) were independent factors associated with MRSA acquisition during hospitalization. The screening and isolation program reduced the acquisition rate by 1.6 % and was found to be cost saving. For the whole study period, the program cost US$129, 916, while it offset hospitalization costs of US$103, 869 and loss of productivity costs of US$50, 453 with −400 $/DALY averted. Discussion This study is the first to our knowledge that evaluates the cost-effectiveness of screeningand isolation of MRSA patients in a tropical country. Another unique feature of the analysis is the evaluationof acquisition rates among specific types of patients (dermatological, HIV and infectious disease patients)and the comparison of the cost-effectiveness of screening and isolation between them. Conclusions Overall our results indicate high MRSA prevalence that can be cost effectively reduced by selective screening and isolation programs in Singapore.